Impact of Climate Change on Crop Yields: Evidence from Irrigated and Dry Land Cultivation in Semi-Arid Region of India - Kalli, Rajesh; Jena, Pradyot Ranjan (Journal of Environmental Accounting and Management, 2026)
With population pressure constantly growing in India the crop productivity is struggling hard to catch up. Erratic rainfall and steady rise in temperature create widely uncertain outcomes for the farming communities. Against this backdrop, the present study has used a climate dataset constructed at a finer spatial level from a southern Indian state namely Karnataka to analyze the yield response of rice and maize crops to climate change. Using a time period from 1992 to 2012, a panel dataset has been made at the district level. The fixed effect regression results show that rice and maize productivity has been impacted adversely due to a steady rise in temperature in the state. The extent of damage is found to be 7% to 10%. Further, the study has also probed the role of irrigation as a climate adaptation strategy and has found out that adverse yield impact is reduced in the presence of irrigation. These findings provide some specific directions for policy framing to curb yield damage arising from climate variability.